Setting the boundaries and scope of practice for the two sister specialities of dentistry: operative dentistry-endodontics and prosthodontics - Farhan Raza Khan (Journal of the Pakistan Medical Association, 2023)
Dental academia in Pakistan has recently achieved an important milestone. The name of Operative Dentistry speciality has been changed to Operative Dentistry & Endodontics (ODE). It was a much-needed change that was first felt about two decades ago. However, with the correction of name, there are certain challenges that this speciality has to manage now. These include improving the curriculum, setting up standards, and lastly, setting up its boundaries and scope of practice as some of its scope overlaps with a sister speciality called Prosthodontics. This overlapping of the boundaries of dental disciplines is a problem that is unique to Pakistan, India, and some East Asian countries where Operative Dentistry or Conservative Dentistry is combined with Endodontics. This paper aims to discuss the objective delineation of dental procedures and suggest a model of peaceful co-existence of sister dental specialities. Keywords: Scope-of-practice regulation, Appointment, Credentialing, Group practice.